2020
DOI: 10.1590/2175-8239-jbn-2020-s106
|View full text |Cite
|
Sign up to set email alerts
|

Good practices recommendations from the Brazilian Society of Nephrology to Peritoneal Dialysis Services related to the new coronavirus (Covid-19) epidemic

Abstract: Considering the new coronavirus epidemic (Covid-19), the Brazilian Society of Nephrology, represented by the Peritoneal Steering Committee, in agreement with the and the Dialysis Department, developed a series of recommendations for good clinical practices for peritoneal dialysis (PD) clinics, to be considered during the period of the Covid-19 epidemic. We aim to minimize the disease spread, protecting patients and staff, and ensuring the quality of the treatment provided and adequate follow-up for PD patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 6 publications
0
4
0
2
Order By: Relevance
“…Considering the hazardous context of SARS-CoV-2 infection, in order to attenuate the spread of the virus in CKD patients undergoing dialysis, a series of safety measures were adopted by hemodialysis centers and clinics to efficiently operate throughout the pandemic (Table 2) [65][66][67][68][69][70][71][72] . Nonetheless, Corbett et al in a cohort study evaluating the epidemiology of COVID-19 in dialysis centers in the United Kingdom revealed that COVID-19 caused an abrupt epidemic in patients and healthcare workers.…”
Section: Patients With Ckd In Dialytic Therapy and Covid-19mentioning
confidence: 99%
“…Considering the hazardous context of SARS-CoV-2 infection, in order to attenuate the spread of the virus in CKD patients undergoing dialysis, a series of safety measures were adopted by hemodialysis centers and clinics to efficiently operate throughout the pandemic (Table 2) [65][66][67][68][69][70][71][72] . Nonetheless, Corbett et al in a cohort study evaluating the epidemiology of COVID-19 in dialysis centers in the United Kingdom revealed that COVID-19 caused an abrupt epidemic in patients and healthcare workers.…”
Section: Patients With Ckd In Dialytic Therapy and Covid-19mentioning
confidence: 99%
“…On the contrary, PD patients, received telemedicine consultation during the COVID-19 pandemic. 24 Moreover, telehealth has played a pivotal role in the current pandemic and should be implemented whenever possible; however, the quality of evidence is controversial. [25][26] Studies evaluating the impact of COVID-19 on PD and HD patients have conflicting results 2,8,22,23,27 .…”
Section: Discussionmentioning
confidence: 99%
“…O grupo HD não conseguiu aderir às recomendações de isolamento, e 16% relatou ter tido contato com a COVID-19 no transporte público a caminho da unidade de diálise. Pelo contrário, os pacientes em DP, receberam consulta por telemedicina durante a pandemia da COVID-19 24 . Além disso, a telessaúde tem desempenhado um papel crucial na atual pandemia e deve ser implementada sempre que possível; no entanto, a qualidade das evidências é controversa 25,26 .…”
Section: Discussionunclassified